2001
DOI: 10.1128/jb.183.14.4323-4329.2001
|View full text |Cite
|
Sign up to set email alerts
|

ISAfe1, an ISL3 Family Insertion Sequence fromAcidithiobacillus ferrooxidansATCC 19859

Abstract: Acidithiobacillus ferrooxidans, formerly Thiobacillus ferrooxidans (24), is a gram-negative bacterium that has been shown to be active in the solubilization of copper and in the processing of refractory gold ores in bioleaching operations (reviewed in references 21 and 36). It is also a major contributor to acid mine drainage in copper and coal mines and in certain natural environments. It is a chemolithotroph, deriving energy and electrons from the oxidation of ferrous iron and/or sulfur and various reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…The identification of the petI and res operons also supports a model for phenotypic switching (10) in which the reversible insertion of ISAfe1 (formerly IST1) into resB results in a mutant phenotype in which cells are unable to utilize Fe(II) as a sole energy and electron source but can still grow in the presence of reduced sulfur (2,16). Insertional inactivation of resB by ISAfe1 could lead to an incorrectly matured cytochrome c, possibly the diheme cytochrome c 4 and/or the cytochrome c 1 encoded by the petI operon, effectively knocking out uphill electron flow through complex III.…”
Section: Fig 1 Map Of the Peti And Res Operons Of A Ferrooxidansmentioning
confidence: 92%
“…The identification of the petI and res operons also supports a model for phenotypic switching (10) in which the reversible insertion of ISAfe1 (formerly IST1) into resB results in a mutant phenotype in which cells are unable to utilize Fe(II) as a sole energy and electron source but can still grow in the presence of reduced sulfur (2,16). Insertional inactivation of resB by ISAfe1 could lead to an incorrectly matured cytochrome c, possibly the diheme cytochrome c 4 and/or the cytochrome c 1 encoded by the petI operon, effectively knocking out uphill electron flow through complex III.…”
Section: Fig 1 Map Of the Peti And Res Operons Of A Ferrooxidansmentioning
confidence: 92%
“…The occurrence of many IS elements almost identical to ISAtc1 and ISAfe1 previously reported to occur in many copies per cell in numerous isolates of A. ferrooxidans, A. thiooxidans, and A. caldus (16,18,24) is not surprising. Furthermore, these IS elements were still highly active and capable of transposition, especially when the plasmids were cloned in E. coli.…”
Section: Re -Mod Isatc1mentioning
confidence: 92%
“…4A and B). The transposase of the IS element found within the arsenic operon most closely resembles (326/399 amino acids, or 81% identity) that of the rooxidans ATCC 19859 (16), and this element has, therefore, been designated an ISAfe1-type element. At the nucleotide level, it is only 77.46% identical to the ISAfe1 sequence.…”
Section: Analysis Of the Region Common To All Three Plasmids (I)mentioning
confidence: 99%
See 1 more Smart Citation
“…From these data, prediction of a number of genes involved in the bioleaching process has been made. [11] In addition, it has revealed that two large mobile genetic elements, [12,13] together with insertion sequence elements, transposons and plasmids, [11,14,15] have tailored the genome of A. ferrooxidans eventually by horizontal gene transfer (HGT). Furthermore, a gene encoding for a functional tyrosyl-tRNA synthetase with higher similarity to the tyrZ gene product from B. subtilis than E. coli tyrS (44 % versus 24 % identity, respectively) was identified.…”
Section: Introductionmentioning
confidence: 99%